Management Of Da'wah Training At Modern Boarding School Al- Hasyimiyah Darul Ulum (PEMADU) In Creating Professional Da'i - Tamanda Siregar; Soiman (TASAMUH : Jurnal Komunikasi dan Pengembangan Masyarakat Islam, 2025)
Management is one of the essential components in da'wah training. This study aimed to determine how to manage da'wah training at Al-Hasyimiyah Darul Ulum Islamic Boarding School (PEMADU) in creating professional Da'i cadres. This research uses descriptive qualitative field methods by collecting data from literature, interviews, and observations. The study results found that the management of da’wah training at the Al-Hasyimiyah Darul Ulum (PEMADU) Islamic Boarding School includes planning, organizing, implementing, monitoring, and evaluating. This shows that the da'wa training at the Al-Hasyimiyah Darul Ulum (PEMADU) Islamic Boarding School has run well. The training material is also appropriate, as the material is given gradually and differently.